1966
DOI: 10.1063/1.1727601
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Electron Capture by Benzene Derivatives

Abstract: We have studied dissociative electron capture in a series of benzene derivatives using the combined swarm—beam method. The benzene derivatives C6H5Cl, o-C6H4Cl2, o-C6H4CH3Cl, C6H5Br, C6D5Br, and o-C6H4CH3Br, capture low-energy (including thermal) electrons dissociatively in a capture process which peaks at about 1 eV and yields only Cl− or Br− ions. The energies (in electron volts) at which the capture cross sections σc(ε) for the ∼1-eV processes peak and the values of σc(ε) (in cm2×1017) at peak energy for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

1968
1968
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(42 citation statements)
references
References 19 publications
3
39
0
Order By: Relevance
“…22, since (i) we account for short-range (other than dipole) interactions in the lower partial waves, which would be important for scattering at higher angles; (ii) our Born corrections employ an overestimated dipole moment magnitude (consistent with the HF description of the target molecule); (iii) our model amounts to an approximate rotationally summed cross section from the rotational ground state of the target, without accounting for thermal averages over the initial rotational states (see Oliveira et al 47 for details); and (iv) we do not correct the cross sections to account for undetected electrons at low scattering angles as described by Lunt et al, 22 although we integrate the Regarding the resonances, the lowest-lying structure in the SMCPP ICS, about 0.7 eV, is related to the nearly degenerate π * (B 1 ) and π * (A 2 ) resonances (see below). The peak position agrees with the experimental TCS 22,23 (0.75 and 0.8 eV, respectively), as well as with the ETS data 14,15 (0.73 eV-0.75 eV) and the DEA data 14,[16][17][18] (∼0.7 eV). There is also agreement for the second structure, arising from the σ * CCl anion state, since the peak at 2.8 eV in the SMCPP ICS is consistent with the experimental data (∼2.5 eV).…”
Section: Experimental Apparatus and Operating Proceduressupporting
confidence: 73%
“…22, since (i) we account for short-range (other than dipole) interactions in the lower partial waves, which would be important for scattering at higher angles; (ii) our Born corrections employ an overestimated dipole moment magnitude (consistent with the HF description of the target molecule); (iii) our model amounts to an approximate rotationally summed cross section from the rotational ground state of the target, without accounting for thermal averages over the initial rotational states (see Oliveira et al 47 for details); and (iv) we do not correct the cross sections to account for undetected electrons at low scattering angles as described by Lunt et al, 22 although we integrate the Regarding the resonances, the lowest-lying structure in the SMCPP ICS, about 0.7 eV, is related to the nearly degenerate π * (B 1 ) and π * (A 2 ) resonances (see below). The peak position agrees with the experimental TCS 22,23 (0.75 and 0.8 eV, respectively), as well as with the ETS data 14,15 (0.73 eV-0.75 eV) and the DEA data 14,[16][17][18] (∼0.7 eV). There is also agreement for the second structure, arising from the σ * CCl anion state, since the peak at 2.8 eV in the SMCPP ICS is consistent with the experimental data (∼2.5 eV).…”
Section: Experimental Apparatus and Operating Proceduressupporting
confidence: 73%
“…Long-lived negative molecular ions have maxima of effective yields at $0.03 eV, similar to the molecular NIs of the nitro-substituted benzene derivatives. 9,25 Evidently, these ions are produced by means of the nuclear excited Feschbach resonance (NEFR). 25 The next compound negative ion resonant (CNIR) state is observed at an energy $0.9 eV.…”
Section: P-cic 6 H 4 Nomentioning
confidence: 99%
“…This CEY is in good agreement with previous data. 9 Comparison of the Cl À CEY with that for SF 6 À shows that the left-hand side of the Cl À CEY has practically the same shape as the left-hand side of the SF 6 À CEY. This means that there are no resonant states below the high intensity maximum at 0.74 eV (Fig.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Nitrobenzene, nitrotoluene and other aromatic nitrocompounds were studied rather early by using electron beam and swarm techniques [9,[12][13][14][15][16]. It was found that these compounds form long-lived molecular anions with lifetimes in the microsecond to millisecond range, in addition they also undergo dissociative electron attachment yielding NO 2 − .…”
Section: Introductionmentioning
confidence: 99%